2014
DOI: 10.1189/jlb.5a0813-463rr
|View full text |Cite
|
Sign up to set email alerts
|

Th22 cells are expanded in multiple sclerosis and are resistant to IFN-β

Abstract: Th1 and Th17 cells have been considered as effectors in mouse EAE and in the human counterpart, MS. Recently, IL-22, a Th17-related, proinflammatory cytokine, has been associated with a new Th cell subset, defined as Th22, involved in chronic inflammatory conditions, such as psoriasis; the role of IL-22 in MS has not yet been elucidated. Here, we report that similar to Th17 cells, the number of Th22 cells increased in the PB and the CSF of RR MS patients, especially during the active phases of the disease. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 38 publications
1
72
2
2
Order By: Relevance
“…Our finding that, similar to observations in the mouse (53), TLR2 activation can promote human Th17 differentiation suggests that peripheral activation of T cells in the presence of microbial TLR1/2 stimuli could drive them to a Th17 phenotype and function. IL-22 has been associated with Th22, a Th subset that is expanded in MS and can react to the myelin autoantigen MBP (54). Th22 cells expressed lower levels of IFNAR1 and were insensitive to IFN-b inhibition, suggesting that expansion of Th22 cells in MS could influence resistance to IFN-b therapy (54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that, similar to observations in the mouse (53), TLR2 activation can promote human Th17 differentiation suggests that peripheral activation of T cells in the presence of microbial TLR1/2 stimuli could drive them to a Th17 phenotype and function. IL-22 has been associated with Th22, a Th subset that is expanded in MS and can react to the myelin autoantigen MBP (54). Th22 cells expressed lower levels of IFNAR1 and were insensitive to IFN-b inhibition, suggesting that expansion of Th22 cells in MS could influence resistance to IFN-b therapy (54).…”
Section: Discussionmentioning
confidence: 99%
“…IL-22 has been associated with Th22, a Th subset that is expanded in MS and can react to the myelin autoantigen MBP (54). Th22 cells expressed lower levels of IFNAR1 and were insensitive to IFN-b inhibition, suggesting that expansion of Th22 cells in MS could influence resistance to IFN-b therapy (54). Because naturally occurring Tregs express higher levels of TLR2 and TLR1 (10,14,24,55), our data indicate that they may preferentially respond to microbial stimuli in vivo by switching to a Th17/Th22 phenotype and function.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Th22 cells in MS has also been previously described [15,16], whereas the differentiation and the role of Th9 cells in the disease have never been investigated.…”
Section: Introductionmentioning
confidence: 96%
“…These cells, like Th17, express elevated levels of CCR6, which is required for their migration into the CNS. 14,15 Despite these findings, little is known about the T-cell behaviour in MS patients during the early stages, mainly during the remission phase, and its relation to clinical and radiological activity. It was pointed out that disease activity in the first 2 years after diagnosis may have a prognostic value.…”
Section: Th1 Cells and Activated Cd8mentioning
confidence: 99%
“…12 However, production of IL-22 may occur in a unique subset of CD4 + T cells, named Th22, regardless of IL-17 release. 13 Study by Rolla et al 14 has demonstrated a high frequency of myelin-specific Th22 cells in MS patients, especially during the active phases of the disease. These cells, like Th17, express elevated levels of CCR6, which is required for their migration into the CNS.…”
Section: Th1 Cells and Activated Cd8mentioning
confidence: 99%